UPAYA ORANG TUA MENGATASI KECANDUAN BERMAIN GAME ONLINE PADA ANAK DI DESA BUATAN II KECAMATAN KOTO GASIB KABUPATEN SIAK - Selvia Rahma Dona; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted in Artificial Village II, Koto Gasib District, Siak Regency, which aimed to find out how the efforts of parents, especially female parents, in overcoming online game addiction in children and how also the efforts of parents to respond to the activities of children who are already addicted to online games. The method used is a qualitative research method carried out with this method because this study will analyze in depth how subjective (parental efforts) who have elementary school-age children addicted to playing online games. The results of the study stated that parents became one of the factors in the occurrence of online game addiction to children in addition to environmental factors, friends and associations are also another factor in online game addiction. Impact. What is caused by playing online games shows more negative impacts. Parents' efforts in overcoming online game addiction by limiting children's time playing games, supporting children's hobbies, and putting children in private tutoring. It is recommended to parents to be able to pay more attention to their children, spend more time with their children. Parents must be able to set when the child's schedule to study and when the child's schedule to play smartphones, and parents must manage the child's time, including bedtime Parents must always accompany their children if they want to play games. Keywords : parental efforts, addicted, game online